Analysis of Profile and Contributing Factors to Non-adherence towards Antibiotics Utilization Among Caregivers of Paediatric Patients - I Komang Agus Bayu Krisnanta; Nani Parfati; Bobby Presley; Eko Setiawan (Faculty of Pharmacy, Universitas Gadjah Mada)
Non-adherence to antibiotic is considered as one of causes of antibiotic resistance. Caregiver plays a vital role to ensure that the paediatric patients adhere to the antibiotic treatment prescribed by physician. This study aimed to analyze the profile and factors contributing to non-adherence behavior among caregivers of pediatric patients. Caregivers of pediatric patients were recruited from one of private clinic in Surabaya. The percentage ratio of medication used to total prescribed medication was calculated to measure adherence, cut-off of 80% was used in this study to categorize adherence and non-adherence. Factors contributing to the non-adherence behavior was identified by intervewing the caregivers and the results was analysed based on Theory of planned behavior as a guide for mapping factors contributing to non-adherence. Twenty-seven out of a total of 38 caregivers (71.05%) categorized as non-adherence to the therapy. Several factors hindered adherence behavior identified in this study were: caregivers’ belief on adverse drug reaction, false belief on the health prognostic, false knowledge about antibiotic, time commitment of caregivers, forgetfulness, sharing medication among family member phenomenon, and type of medicine preparation. Prevalence of non-adherence behavior to antibiotic among community in Surabaya is relatively high and lack of knowledge does not always be the only reason behind it. Other factors that might influence medication non-adherence need to be considered to get better result, instead of only focusing on increasing patient’s knowledge. Further study is needed to identify the best and more effective intervention to improve adherence as preliminary mapping before establishing local or national scale policy.